ANALYSIS OF SELF-CONTROL IN MEDIATING THE INFLUENCE OF THE SOCIAL ENVIRONMENT AND ADOLESCENT PERCEPTIONS OF ADOLESCENT ATARAXIA AT THE NAHDLATUL AT-THULAB IPNU IPPNU: PLS-SEM ANALYSIS - Saputra, Yahya Dwi Marta; Hakim, Ahmad Nu'man; Daryono, Rihab Wit (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This research aims to explore the influence of Adolenscent perceptions and Social Environment on teenagers' Ataraxia, as well as the mediating role of self-control in the context of prayer activities in the Nahdlatul At-Thulab IPNU IPPNU assembly. A quantitative survey method was used involving 60 teenagers in the Nahdlatul At-Thulab IPNU IPPNU prayer assembly, using probability sampling techniques with proportionate stratified sampling techniques. Data was collected through a questionnaire with a Likert scale, and data analysis was carried out using relevant statistical techniques. The research results show that there is a positive influence of Adolenscent perceptions and Social Environment on the results of Teenager Ataraxia, with self-control mediating this relationship. The implications of this research include the importance of developing self-control skills and motivation in prayer meetings. Recommendations for further research include exploring other factors that influence adolescent perception, social environment, and self-control, as well as developing prayer activities to understand the dynamics of adolescent ataraxia.